Kecenderungan individu terhadap penggunaan facebook berkaitan isu politik Malaysia - Nur Shazana, Abdul Rani (2019)
Facebook is a popular alternative platform for youths seeking political information. This is because Facebook is a major tool in politics that is used by youths to expand their political discourse. The study aims to understand how and why the youth acted to express their opinions on political issues in Facebook and vice versa. The research also investigated Facebook's power as a technology in strengthening existing community relationships as well as the emergence of a new community which is a social media-based network. The Media Systems Dependency Theory was applied in this study. This research involves two research methods which is qualitative and quantitative methods. The first phase of the research involved interviewing eight Malaysian youths as active Facebook users on political issues in Malaysia, both from the government and the opposition. Then, a total of 386 questionnaires were used in the second phase to explore their Facebook knowledge and the impact on their political participation. All data were analysed by thematic analysis and applied Partial Least Squares Structural Equation (PLS-SEM). The findings show that youth participation as a Facebook user contributes to decision-makers in the election of national leaders, Facebook is a major source of political information, Facebook can raise awareness on political issues and can act as a catalyst for national issues. The findings show that Facebook plays a role in transforming traditional political landscape and nurturing social networks based on political activism, resulting in increased of political participation among youth. The implication of this study can provide information to stakeholders to interact openly in providing feedback on politics.